1990
DOI: 10.1177/104063879000200415
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Iowae Species-Specific DNA Probe

Abstract: Abstract.A Mycoplasma iowae (MI) species-specific DNA probe (designated pMI-2) of 6.0 kbp (kilobase pairs) was isolated from an MI strain I-695 genomic library prepared in plasmid pUC8 and Escherichia coli strain JM83. When labeled with [32] P by nick translation, the probe hybridized in dot blot assays with 6 reference strains and 8 field isolates of MI but not with 16 other known species of avian mycoplasmas. The pMI-2 probe detected a minimum of 1.5 ng of MI strain I-695 chromosomal DNA. Under identical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There are early descriptions of the experimental use of PCR for detecting MI (Zhao and Yamamoto, 1990;Kempf et al, 1994;Boyle et al, 1995). It is a rapid, sensitive, and simple diagnostic method with Garcia et al (1996) describing the successful development and experimental use of PCR as part of a multi-mycoplasma species test that included MI.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…There are early descriptions of the experimental use of PCR for detecting MI (Zhao and Yamamoto, 1990;Kempf et al, 1994;Boyle et al, 1995). It is a rapid, sensitive, and simple diagnostic method with Garcia et al (1996) describing the successful development and experimental use of PCR as part of a multi-mycoplasma species test that included MI.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…This became known as the Iowa 695 strain of avian mycoplasma. It can also be used to identify some MI strains (Zhao and Yamamoto, 1990;Boyle et al, 1995;Cai et al, 2008). This has mostly been alleviated with the use of polymerase chain reaction (PCR) assays that have allowed the detection of species specific DNA segments.…”
Section: Introductionmentioning
confidence: 99%
“…ield and laboratory studies have identified that Mycoplasma iowae is the etiological agent of reduced hatchability, malabsorption syndrome, mild airsacculitis, leg deformities, and exudative tenosynovitis in turkeys and chickens (15). M. iowae strains isolated from turkeys, chickens, and wild birds were reported in North America, Western Europe, Israel, India, and Pakistan, with an unusual case isolated from aborted apple seeds in France in 1979 (2).…”
mentioning
confidence: 99%